SISTEM INFORMASI UNIT PELAYANAN INFORMASI DAN KELUHAN MASYARAKAT BERBASIS WEB PADA KABUPATEN TANJUNG JABUNG TIMUR : Community Services;Information Systems;Information Services and Community Complaints Unit;Web. - Simorangkir, Lucy; Limia Budiarti, Rike; Lestari, Munjiah (LP2M Universitas Nurdin Hamzah, 2020)
The Information and Complaints Service Unit (UPIK) is a media for receiving and responding to information or input from the public related to government administration and public services to submit complaints, information and suggestions for the development of government services in Tanjung Jabung Timur Regency for the better. The aim is to facilitate the public in notifying or complaining of problems in urban development or government problems and issues related to inadequate public facilities. Because these problems can become obstacles to the progress of a government. During this time the public complaints system in Tanjab Timur Regency still uses sms so that it is less optimal, namely the absence of transparency or openness of information between admin and user. Therefore, it is necessary to create a new system, which is a web-based information service unit and public complaints service system that makes it easy for the public to submit complaints and this system is transparent or there is openness between the admin and user. Input data in the form of fire data, complaint data, attitude violence data, traffic traffic data, critical data, and message data to be processed and the output in the form of fire data reports, complaint data, attitude violence data, and traffic traffic data. By making this information system it is hoped that it can help the people of Tanjab Timur in making complaints or see other information about East Tanjab Regency more easily and transparently and transparently from the admin.